Implementasi Digitalisasi Perbankan di Bank Bengkulu - Rahmi Fitriandanty; Fitri Santi; Rina Suthia Hayu (Universitas Bengkulu, 2022)
Abstract The purpose of the study was to determine the implementation of banking digitalization at Bank Bengkulu. Data collection through interviews with people involved in digitization policy makers at Bank Bengkulu, they are the Independent President Commissioner, President Director, Business Director, Compliance Director and Head of the Information Technology Division. Data analysis using descriptive analysis method and qualitative analysis. The results of the study revealed that the implementation of banking digitization at Bank Bengkulu seen from digital internet banking services, SMS Banking, Phone Banking, Mobile Banking and ATMs had not been fully implemented, due to constraints in OJK regulations. Bank Bengkulu digitization services that have been implemented are SMS Banking, Mobile Banking and ATM. For internet banking, the permit from OJK related to the core capital of banks must be above 1 trillion, while for phone banking it is not yet included in the development plan. ank Bengkulu is very ready to implement more advanced banking digitalization. Bank Bengkulu's banking digitalization development plan in the future is in accordance with the IT Blueprint which is focused on infrastructure transformation and digital transformation. Bank Bengkulu has gradually prepared an independent system, while for systems that cannot be prepared, they will be imported from outside or collaborate with vendors so that the transformation carried out is more effective and saves the digital investment budget. Bank Bengkulu has financial capacity constraints and IT human resource competencies. OJK as a regulator requires Bengkulu Bank to have a core capital of more than 1 trillion to be able to use internet banking services or be included in the book bank category II. Then the competence of human resources to develop the core system is still very limited. It still needs to be developed through training, workshops and internship programs and others. The limited competence of human resources owned by Bank Bengkulu makes the core system of Bank Bengkulu managed by a vendor from PT. Sigma is a subsidiary of Telkom based in Jakarta. However, in the future, it will gradually be managed independently in accordance with the existing human resource capacity Keywords: Implementation, Digitalization, Banking, Bengkulu Bank Abstrak Tujuan penelitian untuk mengetahui implementasi digitalisasi perbankan di Bank Bengkulu. Pengumpulan data melalui wawancara dengan pihak-pihak yang terlibat dalam pengambil kebijakan digitalisasi di Bank Bengkulu yaitu Komisaris Utama Independen, Direktur Utama, Direktur Bisnis, Direktur Kepatuhan dan Kepala Divisi Teknologi Informasi. Analisis data menggunakan metode analisis deskriptif dan analisis kualitatif. Hasil penelitian mengungkapkan bahwa implementasi digitalisasi perbankan di Bank Bengkulu dilihat dari layanan digital internet banking, SMS Banking, Phone Banking, Mobile Banking dan ATM belum sepenuhnya dilaksanakan, karena terkendala peraturan OJK. Layanan digitalisasi Bank Bengkulu yang telah diterapkan adalah SMS Banking, Mobile Banking dan ATM. Untuk internet banking, izin dari OJK terkait modal inti perbankan harus di atas 1 triliun, sedangkan untuk phone banking belum masuk dalam rencana pengembangan. ank Bengkulu sangat siap menerapkan digitalisasi perbankan yang lebih maju. Rencana pengembangan digitalisasi perbankan Bank Bengkulu ke depan sesuai dengan IT Blueprint yang fokus pada transformasi infrastruktur dan transformasi digital. Bank Bengkulu secara bertahap menyiapkan sistem yang mandiri, sedangkan untuk sistem yang tidak dapat disiapkan akan didatangkan dari luar atau bekerjasama dengan vendor sehingga transformasi yang dilakukan lebih efektif dan menghemat anggaran investasi digital. Bank Bengkulu memiliki kendala kapasitas keuangan dan kompetensi SDM IT. OJK sebagai regulator mewajibkan Bank Bengkulu memiliki modal inti lebih dari 1 triliun untuk dapat menggunakan layanan internet banking atau termasuk dalam bank buku kategori II. Kemudian kompetensi SDM untuk mengembangkan core system masih sangat terbatas. Masih perlu dikembangkan melalui pelatihan, workshop dan program magang dan lain-lain. Keterbatasan kompetensi SDM yang dimiliki Bank Bengkulu menjadikan core system Bank Bengkulu dikelola oleh vendor dari PT. Sigma merupakan anak perusahaan Telkom yang berbasis di Jakarta. Namun ke depan secara bertahap akan dikelola secara mandiri sesuai dengan kapasitas SDM yang ada Kata Kunci: Implementasi, Digitalisasi, Perbankan, Bank Bengkulu